Highly efficient oxygen evolution catalysis achieved by NiFe oxyhydroxide clusters anchored on carbon black. Issue 19 (9th May 2022) - Wang, Zhongke; Wang, Yuyang; Zhang, Nan; Ma, Lixia; Sun, Jie; Yu, Can; Liu, Shoujie; Jiang, Ruibin
Abstract : The NiFe-oxyhydroxide/C OER catalyst is prepared through the hydrolysis of nickel and iron salts in the presence of carbon black. It exhibits an overpotential of 269.6 mV at 10 mA cm −2 and a mass activity of 593.1 A g −1 at an overpotential of 320 mV. Abstract : The sluggish kinetics of the oxygen evolution reaction (OER) restrict the efficiencies of renewable energy storage and conversion methods, including water splitting and metal–air batteries. Owing to their abundant misaligned atoms and sub-nanometer sizes, metal oxide/oxyhydroxide clusters supported by good electric conductors are supposed to have superior electrocatalytic activity toward the OER. Herein, highly efficient oxygen evolution catalysis is achieved using NiFe oxyhydroxide clusters anchored on carbon black (NiFe-oxyhydroxide/C). To reach a current density of 10 mA cm −2, the NiFe-oxyhydroxide/C sample with a Ni/Fe molar ratio of 1 : 1 (Ni0.5 Fe0.5 /C) only needs an overpotential of 269.6 mV, which is much smaller than those of amorphous NiFe-oxyhydroxide particles (347.9 mV) and commercial RuO2 (423.3 mV). In particular, the mass activity of Ni0.5 Fe0.5 /C can reach 593.1 A g −1 at a very low overpotential of 320 mV. Experimental characterizations and theoretical calculations indicate that the existence of Ni–O–Fe structures in NiFe-oxyhydroxide/C accounts for its excellent OER activity. Our findings not only provide a novel avenue for the preparation of excellent OER electrocatalysts but they also deepen our understanding of the catalytic mechanisms of NiFe-based OER electrocatalysts.